Which epigenetic and inflammation related biomarkers can identify clinically aggressive prostate cancer - Santos, Pedro Alexandre Álvares Bargão dos (2020)
ABSTRACT: Prostate cancer is a highly prevalent malignancy and a major cause of cancer-related morbidity and mortality. Radical prostatectomy technique remains the major treatment opbon for men with potenbal cure and life expectancy exceeding 10 years. In the very recent 2018 published follow-up of 29 years of SPG4 study (watchful waibng versus radical prostatectomy), men who did RP gained a mean of 2.9 years of life. One of the relevant issues about surgery is its influence in the oncologic prognosis of pabents, namely, the presence of posibve surgical margins and its impact in biochemical recurrence and subsequent treatments. For this reason, we present, in this thesis, a book chapter published in 2015 about the classical open technique with detailed technical specificabons. Nowadays, more and more main urological surgeries are thoroughly robobc. Pabents with biochemical relapse aoer radical prostatectomy are counseled to do salvage radiotherapy directed to prostabc loca and pelvic lymphabc chains, and hormonal therapy within 2 years. In the majority of cases, we do not know if the pabent actually has disease or where it is located. Also, we do not have any independent biomarker that can accurately indicate if the disease will be aggressive and we should treat, or if the tumor is indolent and the pabent can wait safely, without being submiwed to morbid adjuvant treatments. Convenbonally, prostate cancer prognosis evaluabon is mainly based on PSA, surgical margin status, lymph node status, pathological stage and Gleason score. Unfortunately, the prognosbc power of these is, indeed, insufficient. In 2011, we studied the Amadora (Lisbon) Cohort from Hospital Prof. Doutor Fernando Fonseca with 171 pabents, submiwed to retropubic radical prostatectomy between 2000 and 2005. The stabsbcal risk analysis concluded that the presence of PSM in RRP is strongly influenced by pathological stage ≥ pT3a. The presence of PSM and their number increase significantly the risk of BR compared to other factors. In the absence of PSM, the factors that seemed to be crucial and with greater impact on BR were inibal PSA > 10 ng/ml and pathological Gleason score ≥8. The conclusion, thereaoer, and in concordance with evidence, was that it is important to consider inibal PSA pathological Gleason and surgical margins status when making treatment decisions aoer radical prostatectomy. Nowadays, new tools of molecular nuclear imaging are available, namely, 68Ga-PSMAPET/CT, that have accuracy to detect and localize inibal and recurrent disease with very low levels of PSA (≥ 0,2 ng/ml). We are starbng to “see” and to localize prostate cancer. The cons of this nuclear test are probably the costs and the low availability that restricts it to a limited number of cases that can be done per day, especially if no direct access to the generator/reactor is possible. The evolubon of Magne]c Resonance Imaging with its mul]parametric tools, is allowing clinicians to actually visualize the disease, as well. The novel prostate cancer biomarkers, such as liquid biopsies, epigenebc and inflammabon-related biomarkers and its importance are discussed. In this context, we present two manuscripts. The first, an editorial, about a possible novel biomarker and therapeubc target, the Prostate Stem Cell Anbgen (PSCA). The second, a review arbcle about epigenebc and inflammatory biomarkers that is in peer-review in World Journal of Clinical Oncology (WJCO). We think and believe that the genesis and development of prostate cancer is linked to chronic inflamma]on and epigene]c modifica]ons. The new concepts of urinary microbiota and proliferabve inflammatory atrophy (PIA), a prostate cancer precursor, are explained. Owing to the limitabons of current clinical, serologic, and pathologic parameters in predicbng disease inibabon and progression, we sought to invesbgate the prognosbc value of epigenebc and inflammatory biomarkers by immunochemistry on TMA´s of 234 prostabc specimens from two disbnct cohorts: Hospital Professor Doutor Fernando Fonseca in Amadora, Lisbon and Insbtuto Português de Oncologia of Porto. We sought to assess in a retrospecbve way, several biomarkers, namely, prostabc epigenebc biomarkers not so known in prostabc se{ng: the histone modifiers HDAC1, HDAC4 and histone mark H3Ac, and the inflammatory biomarkers CXCR4, CXCR7, CXCL12, that could be representabve of aggressiveness of prostate cancer. We awempted to correlate the biomarkers expression levels with the clinical and pathological features and other variables such as disease-specific survival (DSS), disease-free survival (DFS) and overall survival (OS). Log-rank test and Cox regression model were used to idenbfy which biomarkers were independent predictors of prognosis. Complete informabon was available for 231 pabents and median follow-up bme was 13.7 years. A total of 16 (6.9%) pabents died from PCa and 89 (38,5%) pabents displayed biochemical relapse. Pathological stage (pTStage) and WHO Grade Groups strabfied pabents in respect to DSS (P < 0.0001 and P = 0.011, respecbvely) and to DFS (P=0.004 and P=0.027, respecbvely). Pabents with higher CXCR4 immunoexpression experienced significantly worse DSS compared to pabents with low expression (HR=1.016, 95% CI:1.002-1.031). The same occurred with CXCL12 (HR=0.546 95% CI:0.322-0.926) and H3Ac (HR=1.015, 95% CI: 1.001 - 1.029). No significant effect on DSS was found for the other biomarkers. In what concerns to DFS, the biomarker CXCR4 disclosed stabsbcally significant associabon with this variable. Pabents with higher expression of this biomarker were significantly more prone to experience disease recurrence (HR=1.003, 95% CI: 1.000-1.005). CXCR7 also corroborated stabsbcal evidence of associabon with DFS (HR=1.111, 95% CI:1.032-1.196). No significant effect on DFS was found for the other biomarkers. When adjusted to pTStage and WHO Grade Groups, the majority of the biomarkers lost stabsbcal significance, except pabents with higher immunoexpression of CXCR7. CXCR7 was the only biomarker which maintained independent impact on DFS (HR =1.119, 95% CI:1.032-1.214). No significant effect on OS was found for any other studied variable. From this analysis we concluded that high-level of CXCR7 expression is an independent predictor of poor prognosis aoer surgery and might provide important informabon for pabent management. To answer the quesbon posed by this thesis Which epigeneDc and inflammaDonrelated biomarkers can idenDfy clinically aggressive prostate cancer, we need to have stronger evidence but our results sustain that targebng biomarkers in blood and in urine are capable of early detecbon of PCa. The CXCL12-CXCR4/CXCR7 signaling axis may be a potenbal strategy. The same biomarkers would also be capable of doing pabent strabficabon and, eventually, be a treatment target. If detecbon of acbve inflammatory axis could be made earlier, earlier treatments could be implemented. This data come to meet the issue of immunotherapy in PCa. Prostate cancer seems to be an ideal model for therapeubc cancer vaccines, once prostate is an unessenbal organ with mulbple tumor-associated anbgens as potenbal targets. In general, PCa is an indolent disease that provides enough bme for the anbtumor immune response to be installed. A two phase approach of immune sbmulabon and immune modulabon seems to produce the best results. Many clinical trials are assessing immunotherapy combinabons and some of them in early stages of the disease. Examples are a STAT3 inhibitor trial (Phase I/II NCT01563302) and 2 trials with PSMA (Phase I NCT01723475 and Phase I NCT02991911). Although this thesis was based in a retrospecbve study, we think it was a relevant work, that opens doors to the understanding and evaluabon of prostate cancer behavior. Further invesbgabons must be pursed so that we can use these news tools and substanbally improve our pabent care in the near future. It will be a valuable task to learn how the intensity of CXCL12 and CXCR7 expression in prostate specimens correlates with its serum levels and, in turn, prospecbvely study how these levels relate to cancer aggressiveness and be able to bewer tailor pabent treatment based in a less invasive proceeding.